2000
DOI: 10.1002/1521-4176(200011)51:11<797::aid-maco797>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of coated steels and Mn- and Co-alloyed steels for separator materials on the cathode side in molten carbonate fuel cells

Abstract: The corrosion behavior and the electrical resistivity of the oxide scale that forms on alternative materials for bipolar plates in molten carbonate fuel cells (MCFCs) were investigated. Commercial stainless steels (SS) containing cobalt (Haynes 556) and manganese (Nitronic 30, Nitronic 50, and Nitronic 60) were tested under cathodic MCFC conditions Additionally, 316L SS coated with cobalt by thermal spraying was studied. Oxide‐scale resistivity measurements were coupled with observations of microstructural/com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This oxide structure is formed by the diffusion of alloying elements; with an inner layer consisting of attributed to its higher Mn content. It has been observed that N50, and other steels with high Mn content, form Mn incorporated spinel compounds [37,38]. It has also been shown that the inclusion of larger amounts of Mn improves the oxidation resistance of chromium and iron by stabilizing the surface film formed on the alloy [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This oxide structure is formed by the diffusion of alloying elements; with an inner layer consisting of attributed to its higher Mn content. It has been observed that N50, and other steels with high Mn content, form Mn incorporated spinel compounds [37,38]. It has also been shown that the inclusion of larger amounts of Mn improves the oxidation resistance of chromium and iron by stabilizing the surface film formed on the alloy [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also observed for the steels tested, with 316L steel achieving better contact resistance values compared to 2205 steel with a higher Cr content. Although a higher manganese content was expected to result in the improved conductivity of the passive layer [ 80 ], the LDX steel showed higher values of contact resistance than the 2205 steel.…”
Section: Resultsmentioning
confidence: 99%